Development and Validation of the Loyalty Program Composition Scale - Ercin, Lokman (International Review of Management and Marketing, 2026)
Modern loyalty programs have evolved from simple point systems to complex platforms that combine economic benefits with experiential elements. However, despite the widespread use of loyalty programs, existing measurement tools often focus on single dimensions or binary distinctions and remain insufficient in reflecting the complex nature of contemporary programs. This study aims to develop a valid and reliable "Loyalty Program Composition Scale" to measure this multidimensional structure from the customer's perspective. Data were collected using purposive sampling from consumers actively using the Migros Money loyalty program in Turkey (N = 785). Exploratory factor analysis revealed a five-factor structure (Reward/Incentive, Convenience, Price Advantage, Gamification, and Status). Confirmatory factor analysis demonstrated good model fit. All dimensions exhibited high internal consistency, convergent validity, and discriminant validity. Criterion validity was established through significant positive correlations with loyalty program satisfaction. This scale fills gaps in the national and international literature by integrating traditional economic benefits with contemporary elements such as gamification and status, offering researchers and practitioners the potential for a comprehensive diagnostic tool to evaluate and design effective loyalty programs.